PENINGKATAN KOMPETENSI LITERASI SISWA PAKET B DAN PAKET C DI PKBM MENTARI FAJAR MELALUI PELATIHAN LITERASI DIGITAL - Sumarjaya, I.W.; Joni, M.; Sibarani, J.; Wibawa, I.G.A. (Buletin Udayana Mengabdi; Vol 21 No 3 (2022): Buletin Udayana Mengabdi, 2022)
A community learning centre is a nonformal education that runs independently by and for community who are unable to finish formal education for any reasons. One of the challenges faces by students at the PKBM Mentari Fajar is lack of digital literacy. The Fourth Industrial Revolution which is indicated by disruption in information technology, connectivity of devices to the Internet known as Internet of Things (IoT), artificial intelligence’s domination, and cultural changes force students to adapt themselves in new paradigm of learning. This community service aims to strengthen the foundation of digital literacy for students of Paket B and C at PKBM Mentari Fajar though workshop. This material of the workshop includes various topics such as using Google, checking validity of news, creating digital contents, and sharing news and digital content responsibly. The workshop was attended by ten students. During the workshop the students directly apply what the presenters demonstrate so that there is a two-way communication. At the end of the workshop, the team evaluates the workshop and gathers feedback from the students. The evaluation results suggest that 80% of the participants say that the workshop can improve their digital literacy especially creating and sharing digital content. Keywords: community learning centre, literacy, digital literacy, the fourth industrial revolution, digital intelligence